The unbalanced dragon: China's uneven provincial and regional FDI performance - Karl P. Sauvant; Chen Zhao; Xiaoying Huo (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
This Perspective ranks all Chinese provinces in terms of their performance in attracting foreign direct investment, examines the reasons for the high unevenness of this performance and makes some policy suggestions on how to deal with it.
Keywords: 330